Application of the EOQ (Economic Order Quantity) Method in Determining Chemical Supplies in PT. Semen Indonesia - Hidayat Hidayat (Universitas Trunojoyo Madura, 2020)
The competition among products has become commonplace in the industrial world in Indonesia. PT. Semen Indonesia is a company with extraordinary development prospects. Quality control is needed in order to control the product so that when it arrives at the consumer the product is in its best condition, or when the product is still in process, production can be maximized. The method used in this research is Economic Order quantity (EOQ). Based on the resercah, the number of orders for each ingredient is for ammonium nitrate 1, barium chloride 1, ethanol 3, glycerol 1, hydrocloric acid 2, sodium hydroxide 3, strontium nitrate 2. Then, the ROP point or time to reorder each ingredient is for ammonium nitrate 2, barium chloride 4, ethanol 33, glycerol 16, hydrocloric acid 21, sodium hydroxide 4, strontium nitrate 13.Keywords: EOQ (Economic Order Quantity), Chemical Supplies, PT.Semen Indonesia